Construction of Bi2WO6/CoAl-LDHs S-scheme heterojunction with efficient photo-Fenton-like catalytic performance: Experimental and theoretical studies. (March 2022) - Shao, Binbin; Liu, Zhifeng; Tang, Lin; Liang, Qinghua; He, Qingyun; Wu, Ting; Pan, Yuan; Cheng, Min; Liu, Yang; Tan, Xiaofei; Tang, Jing; Wang, Hou; et al.
Abstract: The photo-Fenton-like catalytic process has shown great application potential in environmental remediation. Herein, a novel photo-Fenton-like catalyst of Bi2 WO6 nanosheets decorated hortensia-like CoAl-layered double hydroxides (Bi2 WO6 /CoAl-LDHs) was synthesized via hydrothermal process. The optimized Bi2 WO6 /CoAl-LDHs composite performed the high-efficiency photo-Fenton-like catalytic performance for oxytetracycline (OTC) removal (98.47%) in the mediation of visible-light and H2 O2 . The comparative experiment, technical characterization and density functional theory calculation results indicated that the efficient photo-Fenton-like catalytic performance of Bi2 WO6 /CoAl-LDHs was attributed to the synergistic action of the Fenton-like process of cobalt ions in CoAl-LDHs, an internal electric field and the S-scheme heterojunction form between Bi2 WO6 and CoAl-LDHs, which could significantly promote the active substance formation and the photocatalytic process in the catalytic system. This study will stimulate the new inspiration of designing the efficient catalytic system for environmental remediation and other fields. Graphical abstract: Image 1 Highlights: Hortensia-like Bi2 WO6 /CoAl-LDHs composite was synthesized via hydrothermal process. Optical-electrical properties and H2 O2 adsorption behavior of samples were calculated by DFT. Bi2 WO6 /CoAl-LDHs composite exhibited high photo-Fenton-like catalytic activity of antibiotic. An internal electric field and S-scheme heterojunction form between Bi2 WO6 and CoAl-LDHs.